Combined Effects of Oxidation, Moisture, and Freeze–Thaw on Asphalt Mixtures. Issue 12 (December 2020) - Bazuhair, Rabeea W.; Howard, Isaac L.; Middleton, Alex; Jordan, Walter S.; Cox, Ben C.
This article demonstrates the need to laboratory condition asphalt mixtures to simulate combined environmental effects and then to test unconditioned and conditioned specimens in a manner that damage from these environmental effects can be accumulated. The current state-of-the-art for evaluating asphalt mixtures for use on projects relies on either single-mechanism laboratory conditioning such as oxidation in AASHTO R30, or test methods that cannot accumulate combined effects such as indirect tensile strength in AASHTO T283. This article evaluated hundreds of laboratory-conditioned and field-aged specimens in a hot and no-freeze climate to demonstrate a laboratory conditioning protocol that was able to simulate at least 4 years of field aging, whereas conventional single-mechanism protocols were not. Temperature and moisture conditions within asphalt mixtures were measured over time and used as part of the assessment. The conditioning protocol that showed the most promise consisted of combined exposure to oxidation, moisture, and freeze–thaw mechanisms. The specific combined-effects conditioning protocol used here was 5 days of oxidation at 85°C, 14 days of moisture while submerged in 64°C water, and one freeze–thaw cycle. Other combined-effects protocols could be more suitable for other environments or situations; the main point of this article is that inclusion of oxidation, moisture, and freeze–thaw conditioning into one protocol is promising. The environmental conditions and mechanical property test data presented here suggest the asphalt industry needs to be harsher on mixes during laboratory evaluations, and that combined environmental effects conditioning should be given implementation consideration.